2015
DOI: 10.1039/c4gc01752h
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of oxygen and a piranha solution for eco-friendly production of highly conductive graphene dispersions

Abstract: An ecofriendly approach for graphene fabrication is developed, where no toxic and metal containing compounds were used and no toxic byproducts were generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The NCs can be dispersed in a mixed solution of H 2 O 2 and H 2 SO 4 followed with mechanical stirring. According to literatures, the strong oxidizing capability stems from the highly reactive atomic oxygen generated from H 2 O 2 with the existence of H 2 SO 4 . The atomic oxygen will attack the CC bonds in the backbone of PVP molecule, and break the long chain into short molecular pieces that can easily dissolve into the solution .…”
Section: Resultsmentioning
confidence: 99%
“…The NCs can be dispersed in a mixed solution of H 2 O 2 and H 2 SO 4 followed with mechanical stirring. According to literatures, the strong oxidizing capability stems from the highly reactive atomic oxygen generated from H 2 O 2 with the existence of H 2 SO 4 . The atomic oxygen will attack the CC bonds in the backbone of PVP molecule, and break the long chain into short molecular pieces that can easily dissolve into the solution .…”
Section: Resultsmentioning
confidence: 99%
“…Then, 20 g of joss fly ash was mixed in the prepared H 2 SO 4 acid solution. The above pretreatment with a mildly acidic solution was performed to remove carbon and other toxic materials from the ash [13][14][15][16][17] . The mixture was stirred for 2 hours at 45 °C on a heating plate.…”
Section: Acidic Treatment Of Joss Fly Ashmentioning
confidence: 99%
“…For example, a short-term exposure to DMF has been observed to damage the liver in animals and in humans. 40 Savaram et al 41 reported an eco-friendly method for the preparation of graphene avoiding the use of chemical oxidants and reductants. Although some success was achieved, the method proposed, however, required multi-steps and used the SO 4 2− -graphite intercalation compound as the carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the whole process is time-consuming and may take several days to be completed. 41 Exfoliation of graphite may also be achieved by applying a potential to graphite feed materials immersed in an electrolyte. In most of these methods, the graphite feed material immersed in a room temperature electrolyte is connected to the positive pole of a power source.…”
Section: Introductionmentioning
confidence: 99%